1980
DOI: 10.1073/pnas.77.2.970
|View full text |Cite
|
Sign up to set email alerts
|

Independent lines of evidence suggesting a major gap junctional protein with a molecular weight of 26,000.

Abstract: Several polypeptides have been described in the past as components of gap junction fractions. Of these, a peptide of Mr 26,000 is found in gap junctions isolated from livers of different species under conditions that minimize proteolysis. Tryptic digestion of purified "intact" junctions causes the rapid disappearance of this peptide with a concomitant appearance of a band of Mr 10,000, which has previously been found to be characteristic of junctional fractions isolated with the aid of proteolytic treatment. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 14 publications
(13 reference statements)
1
35
0
Order By: Relevance
“…wt. 26 000) of lens bound to isolated lens junctions, Paul and Goodenough (1983) showed that similar antisera bound only to non- consistent from a given source (e.g., 1-2 /4g/g wet weight mouse liver no matter whether starting from a crude homogenate or a post-mitochondrial pellet) and varies in preparations from different sources, as would be expected from freeze fracture studies; liver > V79 cells > BHK cells (Yancey et al, 1978(Yancey et al, , 1982Revel et al, 1971 (Hertzberg and Gilula, 1979;Henderson et al, 1979;Finbow et al, 1980;Nicholson et al, 1981;Traub et al, 1982) or this latter may be a dimeric form of the 16 K protein. This does not appear to be the answer, at least in the case of the 28 K protein isolated by Nicholson et al (1981).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…wt. 26 000) of lens bound to isolated lens junctions, Paul and Goodenough (1983) showed that similar antisera bound only to non- consistent from a given source (e.g., 1-2 /4g/g wet weight mouse liver no matter whether starting from a crude homogenate or a post-mitochondrial pellet) and varies in preparations from different sources, as would be expected from freeze fracture studies; liver > V79 cells > BHK cells (Yancey et al, 1978(Yancey et al, , 1982Revel et al, 1971 (Hertzberg and Gilula, 1979;Henderson et al, 1979;Finbow et al, 1980;Nicholson et al, 1981;Traub et al, 1982) or this latter may be a dimeric form of the 16 K protein. This does not appear to be the answer, at least in the case of the 28 K protein isolated by Nicholson et al (1981).…”
Section: Discussionmentioning
confidence: 93%
“…Under these conditions, nuclei and cytoskeletal elements remain intact and can thus be removed by low speed centrifugation. The procedure then uses adaptations of existing techniques to remove contaminating proteins (Finbow et al, 1980) (Finbow, Lane, Shuttleworth and Pitts, submitted). The method has been applied to mouse (Figures 3 and 4), rat ( Figure 11) and chicken liver, mouse heart, brain and uterus and to cultured BRL cells (Figures 3 and 4 during purification is electron microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gap junctions can be isolated by subcellular fractionation following alkali or detergent treatment (10,11). While there are some discrepancies, it is generally agreed that the constituent protein is z27 kDa (cf.…”
mentioning
confidence: 99%
“…No such studies have been reported yet, although much of the present controversy regarding the protein components of functional gap junctions [30] could be resolved if functional reconstitution could be demonstrated.…”
Section: Discussionmentioning
confidence: 99%